Willingness to test for BRCA1/2 in high risk women: Influenced by risk perception and family experience, rather than by objective or subjective numeracy? - Talya Miron-Shatz; Yaniv Hanoch; Benjamin A. Katz; Glen M. Doniger; Elissa M. Ozanne (Judgment and Decision Making, 2015)
Genetic testing for breast and ovarian cancer can help target prevention programs, and possibly reduce morbidity and mortality. A positive result of BRCA1/2 is a substantial risk factor for breast and ovarian cancer, and its detection often leads to risk reduction interventions such as increased screening, prophylactic mastectomy and oophorectomy. We examined predictors of the decision to undergo cancer related genetic testing: perceived risk, family risk of breast or ovarian cancer, and numeracy as predictors of the decision to test among women at high risk of breast cancer. Stepwise regression analysis of survey responses from 459 women registered in the Cancer Genetics Network revealed greater likelihood to test for women with more family history, higher perceived risk of mutation, or Ashkenazi descent. Neither subjective nor objective numeracy was associated with the decision to test, although we replicated an earlier finding that subjective numeracy predicted willingness to pay for testing. Findings underscore the need for genetic counselling that disentangles risk perception from objective information to promote better decision-making in the context of genetic testing. Highlighting these factors is crucial for public health campaigns, as well as to clinic-based testing and direct-to-consumer testing.